Hepatic gluconeogenesis in rats trained to eat a single meal daily. Role of eating periodicity and the amount of food ingested in the last meal - Batista, Márcia R.; Vasconcelos, Márcio S.; Rebola, Vinícius D.; Galletto, Ricardo; Curi, Rui; Bazotte, Roberto B. (My University, 2001)
Rats trained to eat a single daily meal (MF rats), from 8:00-10:00 a.m., increased food intake from the 1 st to the 12 th (125%) day of feeding training. In this work we compared the influence of the higher food ingestion in the last meal and feeding training on hepatic gluconeogenesis. Thus, rats at the 1 st (MF 1st day-5g group) and 13 th day (MF 13th day-5g group) of training, refed with a fixed amount of food (5g) were employed. In addition, a third group of MF rats, refed on day 12 with 75% (12g) of the food ingested by MF rats on the 13 th day of the feeding training (MF 13th day-12g) was included. The experiments were performed at 22 h after meal (8:00 a.m.). Our results demonstrated that feeding training had a crucial role in determining gluconeogenesis from pyruvate (5 mM). Additionally, gluconeogenesis from L-glutamine (5 mM) was influenced by periodicity of eating and the amount of food ingested in the last meal. In contrast, gluconeogenesis from L-alanine (5 mM) was not influenced by both factors. In conclusion, our findings suggested that the hepatic gluconeogenesis was influenced by food ingestion and/or feeding training depending of the substrate investigated. These effects on gluconeogenesis may have implications for use in diabetic regimens.
Keywords: Eating schedules; Feeding training; Food intake; Gluconeogenesis; Implications in diabetes; L-glutamine and L-alanine and gluconeogenesis; Periodicity of eating; alanine; glutamine; pyruvic acid; animal experiment; animal model; controlled study; diabetic diet; feeding; food intake; gluconeogenesis; liver metabolism; male; nonhuman; priority journal; rat; Adaptation, Physiological; Animals; Blood Glucose; Eating; Glucose; Lactates; Liver; Liver Glycogen; Male; Periodicity; Rats; Rats, Wistar; Urea